Ensuring the functioning of cyberspace in Ukraine: Legal and technical aspects - Sopilko, Iryna (2024)
The authors studied in detail the technical, social, and legal features of the functioning of cybernetic space. The study gives definitions of the cybernetic domain (space) and related terms, such as information space (sphere), cybersecurity, information security, and the like, it indicates goals, objects, and subjects of interaction in cyberspace. Separately considered are its elements such as uncertainty, deterritoriality and the plurality of actors. In the course of this scientific study, the approaches of scholars who researched the cybernetic domain and related categories were analyzed, appropriate conclusions were made on the basis of their work, and the conceptual basis of the work was formed. The authors provide options for solving problems that arise during the use of cyberspace and the information sphere in general, as well as recommendations for ensuring the cybernetic and information security of the state of Ukraine. The methodological basis for this study was the generally recognized criteria of scientific objectivity, as well as other general scientific research methods that provide a comprehensive analysis of cyberspace as an objective new, fourth domain in a range of air, water, and land spaces of Ukraine. The recommendations and suggestions given by the authors of this scientific paper, as well as the conclusions drawn by them, will help coordinate information policy so that Ukraine can become a worthy member of the global information space, and directly cyberspace based on equality and independence.